Bargained liberalisation: the labour movement policy-making and transision in Zambia and South Africa. - Adler, Glen; Webster, Eddie (My University, 1994)
The authors offer a social democratic alternative to neo-liberalism. First, liberalisation must be accompanied by social policies that minimise socialcosts. Second, policies must be designed with a view towards growth, and finally, policies must be formulated and implemented through corporatist-style consultation and negotiation beyond the state and parliament to include unions, employers and other interest groups. "Concertation" is central to their argument: it subjects the reform strategy to the competitive interplay of political forces, improves policy outcomes, builds support for the continuation of reforms, and helps consolidate democratic institutions.
Africa Studies Seminar series. Paper presented 4th August, 1994.
Keywords: Labor. South Africa; Labor. Zambia; Collective bargaining. South Africa; Collective bargaining. Zambia